دور السياسة الجنائية المعاصرة بالمملكة العربية السعودية في مواجهة الفساد المالي والإداري - السبيعي، محمد بن فهد علي الجضعي (جامعة الشارقة, 2023)
مما لا شك فيه أن ظاهرة الفساد الإداري والمالي أصحبت من القضايا التي تفرض نفسها على الصعيد المحلي والدولي، باعتبار ها أصبحت معوقا أساسيا ينعكس على التنمية المجتمعية في مختلف مجالاتها. وبالنظر للجريمة إذا أجزمنا أنها ترتكب عادة من الفقراء أو المحرومين وفق المفهوم التقليدي لها، فإن واقع اليوم في ظل عصر العولمة، يشير إلى أن الجريمة يمكن أن ترتكب من أشخاص ذوي سلطة أو من الأشخاص المتحكمين سياسيا واقتصاديا، الأمر الذي جعل تسخير مواقع السلطة وأجهزة الدولة لتحقيق منافع شخصية بديلا عن دورها الرئيس في خدمة مصلحة المجتمع. فكان لا بد من مواجهة ظاهرة الفساد المالي والإداري بمجموعة من الوسائل والتدابير التي تقوم بها الدولة من أجل مواجهة جرائم الفساد، وبناء عليه جاءت هذه الدراسة مبينة لدور السياسة الجنائية في مواجهة الفساد الإداري والمالي السياسة سواء على المستوى المحلي أو الدولي، وفي ختام الدراسة توصلنا لعدة نتائج وتوصيات نتمنى أن نكون قد وفقنا فيما توصلنا إليه. There is no doubt that the phenomenon of administrative and financial corruption has become one of the issues that impose itself at the local and international levels; as it has become a major obstacle that affects societal development in its various fields. If we assume that it is usually committed by the poor or the deprived according to its traditional concept, the reality of today in the era of globalization indicates that the crime can be committed by people with authority or people who have political and economic powers. This made possible the use of positions of authority and state agencies to achieve personal gains as a substitute for its main role in serving the interest of society. Therefore, it is necessary to confront the phenomenon of financial and administrative corruption with a set of means and measures that the state undertakes to confront corruption crimes. Consequently, this study sheds light on the role of criminal policy in confronting administrative and financial corruption, whether at the local or international level. The research concluded with several results and recommendations. We hope that we have succeeded in our findings.
Keywords: الفساد الإداري -- السياسات الجنائية -- قانون العقوبات -- القانون السعودي